Combined Implant and Tooth Support: An Up-to-Date Comprehensive Overview - Mahmoud K. Al-Omiri; Maher Al-Masri; Mohannad M. Alhijawi; Edward Lynch (International Journal of Dentistry)
Objectives. This article presents a review on the concerned topics and some considerations related to the concept of splinting teeth and implants in the rehabilitation of partial edentulism. Study Selection. An electronic PubMed/MEDLINE and manual search of identified articles and reviews as well as clinical, laboratory, and finite element studies was performed in this project. Due to the shortage in within-subject, long term, randomized, controlled clinical trials regarding the subject a meta-analysis was not possible. Results. Although surrounded with some controversy, joining teeth and implants during the rehabilitation of partial edentulism provides the clinicians with more treatment options where proprioception and bone volume are maintained and distal cantilevers and free end saddles are eliminated. It makes the treatment less complex, of less cost, and more acceptable for the patient. Conclusions. Whenever suitable and justified, combining implant and tooth support might be recommended as an alternative during rehabilitation of partial edentulism. Based on the literature, clinical tips and suggestions were recommended to increase the success of this treatment.